HUG meeting - Fellman, Jack (Printed Circuit Fabrication, 1999)
The Hot Air Leveling User Group met at Manchester, NH, for its third meeting of 1999. More than 42 members and guests attended and listened to the results of Phase II testing and the state of the global lead-free solder program. A presentation on the first commercial lead-free solver, CASTIN, was made. A hot air leveling defect guide was distributed for comments by members. Also held was a thorough discussion of suggestions for Phase III testing.